2017
DOI: 10.1074/jbc.m117.777219
|View full text |Cite
|
Sign up to set email alerts
|

Restricting the conformational freedom of the neuronal nitric-oxide synthase flavoprotein domain reveals impact on electron transfer and catalysis

Abstract: Edited by Ruma BanerjeeThe signaling molecule nitric oxide (NO) is synthesized in animals by structurally related NO synthases (NOSs), which contain NADPH/FAD-and FMN-binding domains. During catalysis, NADPH-derived electrons transfer into FAD and then distribute into the FMN domain for further transfer to internal or external heme groups. Conformational freedom of the FMN domain is thought to be essential for the electron transfer (ET) reactions in NOSs. To directly examine this concept, we utilized a "Cys-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…As depicted in Scheme 1, FAD A 3 FMN A could occur in either open or closed conformation because studies have shown that the FMN domains are flexible, and this flexibility plays a vital role in electron transfer between the FMN, FAD, and heme. For example, restricting the freedom of the motion of the FMN domain greatly impairs the electron transfer of FMN as demonstrated elegantly in rat POR and the reductase domain of nNOS (27,28). As we have shown by 2D EM, the architecture of the BMR is a compact globular protein where the FMN and FAD domains are in proximity.…”
Section: Architecture Of Dimeric Cyp102a1mentioning
confidence: 87%
“…As depicted in Scheme 1, FAD A 3 FMN A could occur in either open or closed conformation because studies have shown that the FMN domains are flexible, and this flexibility plays a vital role in electron transfer between the FMN, FAD, and heme. For example, restricting the freedom of the motion of the FMN domain greatly impairs the electron transfer of FMN as demonstrated elegantly in rat POR and the reductase domain of nNOS (27,28). As we have shown by 2D EM, the architecture of the BMR is a compact globular protein where the FMN and FAD domains are in proximity.…”
Section: Architecture Of Dimeric Cyp102a1mentioning
confidence: 87%
“…We know that the chaperone Hsp90 participates in sGC maturation by bind-ing directly to apo-sGC␤. Its binding prevents apo-sGC␤ from forming a heme-free sGC␣/␤ heterodimer and also enables heme insertion into apo-sGC␤ in an ATP-dependent process (15,16). However, how heme is delivered to apo-sGC␤ remains unclear.…”
mentioning
confidence: 99%
“…For instance, congenital dysplasia of the ENS leads to congenital megacolon (Hirschsprung disease) and primary achalasia, whereas neurodegenerative ENS alterations can lead to the disorders such as Alzheimer, Huntington, and Parkinson diseases[ 16 , 17 ]. The secondary alterations in the ENS also result in inflammatory infiltrates or immune system pathologies such as irritable bowel syndrome[ 18 ], idiopathic enteric gangliosidosis[ 19 ], paraneoplastic syndrome[ 20 ], slow transit constipation[ 21 ], severe acute pancreatitis[ 22 ], diabetes mellitus[ 23 , 24 ], and UC[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be concluded that as a messenger of information transmission between the NOS-positive neurons and GI SMCs, increased NO can reduce the Ca 2+ influx and directly promotes smooth muscle relaxation. In addition, studies have confirmed that NO can inhibit muscle contraction by inhibiting the release of excitatory transmitters[ 23 , 36 ]. Therefore, NO-mediated reduced contractility of the intestinal smooth muscle might be one of the important mechanisms contributing to colonic dysmotility[ 9 , 37 ].…”
Section: Discussionmentioning
confidence: 99%